2007
DOI: 10.1002/hep.21933
|View full text |Cite
|
Sign up to set email alerts
|

Sustained complete response and complications rates after radiofrequency ablation of very early hepatocellular carcinoma in cirrhosis: Is resection still the treatment of choice?

Abstract: If liver transplantation is not feasible, partial resection is considered the treatment of choice for hepatocellular carcinoma (HCC) in patients with cirrhosis. However, in some centers the firstline treatment for small, single, operable HCC is now radiofrequency ablation (RFA). In the current study, 218 patients with single HCC < 2.0 cm (very early or T1 stage) underwent RFA. We assessed 2 primary end points that could be easily compared with those reported for resective surgery: (1) the rate of sustained, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
693
7
19

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 983 publications
(751 citation statements)
references
References 47 publications
32
693
7
19
Order By: Relevance
“…An RCT demonstrated that the number of treatment sessions was fewer with RFA than with microwave coagulation [298], although the rates of complete therapeutic effect, major complications, and local tumor progression were not statistically different between the two therapies. In RFA, survival rates have been reported to be 39.9-68.5% at 5 years [299][300][301][302][303][304] and local tumor progression rates to be 2.4-16.9% [299][300][301]304]. Mortality and morbidity rates of RFA have been reported to be 0.9-7.9% and 0-1.5%, respectively [300][301][302][303][304][305].…”
Section: Local Ablation Is a First-line Treatment Of Unresectable Smmentioning
confidence: 99%
“…An RCT demonstrated that the number of treatment sessions was fewer with RFA than with microwave coagulation [298], although the rates of complete therapeutic effect, major complications, and local tumor progression were not statistically different between the two therapies. In RFA, survival rates have been reported to be 39.9-68.5% at 5 years [299][300][301][302][303][304] and local tumor progression rates to be 2.4-16.9% [299][300][301]304]. Mortality and morbidity rates of RFA have been reported to be 0.9-7.9% and 0-1.5%, respectively [300][301][302][303][304][305].…”
Section: Local Ablation Is a First-line Treatment Of Unresectable Smmentioning
confidence: 99%
“…RFA has recently gained wide acceptance worldwide, mainly due to its relatively low level of invasiveness, ease of use and effectiveness (9,10). The incidence of local tumor progression of HCC reportedly ranges between 0.9 and 31.3% (5,9,(11)(12)(13)(14)(15)(16)(17)(18). Local tumor recurrence may occur due to untreated satellite lesions, which are too small to detect on imaging prior to RFA (19).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, when HCC recurs and further treatment is no longer possible, liver transplantation (LT) may be considered as salvage LT. 4 There are drawbacks of pre-LT treatment for HCC during the waiting period. Dissemination 5 and implantation 6 may occur after puncture of HCC and they may form tumors after the administration of immunosuppressive drugs.…”
Section: Introductionmentioning
confidence: 99%